2008
DOI: 10.1242/jcs.016881
|View full text |Cite
|
Sign up to set email alerts
|

A dual role for IQGAP1 in regulating exocytosis

Abstract: Polarized secretion is a tightly regulated event generated by conserved, asymmetrically localized multiprotein complexes, and the mechanism(s) underlying its temporal and spatial regulation are only beginning to emerge. Although yeast Iqg1p has been identified as a positional marker linking polarity and exocytosis cues, studies on its mammalian counterpart, IQGAP1, have focused on its role in organizing cytoskeletal architecture, for which the underlying mechanism is unclear. Here, we report that IQGAP1 associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
173
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(187 citation statements)
references
References 55 publications
(89 reference statements)
13
173
0
1
Order By: Relevance
“…In addition, it could be interesting to better characterize the role of the cellular factor IQGAP1 which is required for Salmonella uptake and acts following an interaction with actin and the RhoGTPases Rac1 and Cdc42 . Indeed, IQGAP1 is known to regulate actin architecture and interestingly, it also seems to act as a regulator of exocytosis by interacting with Exo70 (Rittmeyer et al, 2008). IQGAP1 could thus be one of the missing links between actin rearrangement and membrane fusion during Salmonella entry.…”
Section: Subversion Of Exocytosis Machinery and Membrane Fusion Durinmentioning
confidence: 99%
“…In addition, it could be interesting to better characterize the role of the cellular factor IQGAP1 which is required for Salmonella uptake and acts following an interaction with actin and the RhoGTPases Rac1 and Cdc42 . Indeed, IQGAP1 is known to regulate actin architecture and interestingly, it also seems to act as a regulator of exocytosis by interacting with Exo70 (Rittmeyer et al, 2008). IQGAP1 could thus be one of the missing links between actin rearrangement and membrane fusion during Salmonella entry.…”
Section: Subversion Of Exocytosis Machinery and Membrane Fusion Durinmentioning
confidence: 99%
“…Matrix metalloprotease accumulation at specific points of contact may require polarized vesicle trafficking. Recently, Chavrier and collaborators showed that the exocyst regulates the exocytosis of matrix metalloproteases in invasive breast carcinoma cells in combination with the Cdc42 effector IQGAP1, the expression of which is highly increased in a variety of cancers (Rittmeyer et al, 2008;Sakurai-Yageta et al, 2008).…”
Section: Hijacking Of the Domain-identity Machinerymentioning
confidence: 99%
“…В свою очередь перестройка актина в значительной степени опреде-ляет подвижность клеток и их способность к миграции [16][17][18]. Другой функцией, выполняемой локализо-ванным на мембране IQGAP1 в околомембранном пространстве, является модуляция экзоцитоза [19]. Поскольку в процессе экзоцитоза в околоклеточное пространство выбрасываются в том числе и матрикс-ные протеиназы, IQGAP1 может быть регулятором перестроек внеклеточного матрикса и ассоциирован-ной с ними клеточной инвазии [20].…”
Section: +unclassified